Hubungan Antara Persepsi Pengelola Akademik Tentang Total Quality Management (Tqm) Dengan Pengintegrasiannya Dalam Kurikulum Pendidikan Tinggi Di Universitas Negeri Jakarta - Umi Widyastuti; Ati Sumiyati; - Maisaroh (Universitas Negeri Yogyakarta, 2009)
Total Quality Management (TQM) is recognized as management approach that concern with customer satisfaction, continuous improvement, team work and leadership. Through implementation of TQM, organizations should be able to improve their performance. This research is conducted to analyze the relation between academic managements perceptions about TQM in undergraduate education with its integration on curriculum, which is tested with product moment correlation, and to know the difference perception about TQM related with its integration on curriculum, between respondent who has identified their customers and who has no, tested with t-test. This research shown there is positive correlation between academics managements perceptions about TQM with its integration on curriculum. It is significant at 95% confidence level. Based on data analysis, the most important indicator that defines academics managements perceptions about TQM is awareness and attitude toward TQM principal including team work, continuous improvement, leadership and focus on customer.This research also proved that there is no difference perception about TQM related with its integration, between respondent who has identified their customers and who has not yet. Because both of them have high awareness and attitude toward TQM principal.